Enhancing Security and Consistency for Cloud Databases - M., Monisha; V., Narmathadevi; Hanirex, D. Kerana (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
Cloud computing is one of the most important research area. The cloud information don't seem to be safe and secured, because the third parties will access and acquire the knowledge from cloud at any time and will misuse the data or information of a particular user or organization and thus it is concerned, the information stored in cloud should come with the guarantee of security. The effectiveness of the planned design is evaluated through theoretical analysis and intensive experimental results supported a model implementation subject to the TPC-C (Transaction Processing Control) normal benchmark for various numbers of purchasers and network latencies. Information and table information area unit encrypted through constant encoding key before being saved. This encoding secret is known as a passkey. Only trusted clients that already know the key will rewrite the information and acquire data that is necessary to code and rewrite tenant knowledge. Each information is retrieved by purchasers through associated ID. The ID which is generated by the Message Authentication Code (MAC) function to the name of the object (database or table) described by the corresponding row. Deterministic MACfunction allows clients to retrieve the information of a given table by knowing its plaintext name. The advantage during this design is to boost smart Quality of Service (QoS) and Distributing knowledge among completely different suppliers and taking advantage of secret sharing.